A global analysis of strengths and weaknesses in our scientific knowledge of tropical forest restoration - Viani, Ricardo A. G.; Reid, J. Leighton (Restoration ecology, 2025)
Tropical forest regions are home to ambitious large‐scale restoration programs, such as Initiative 20 × 20 and AFR100. Concomitantly, much research has been done in these regions in recent decades. We performed a systematic review of scientific publications on tropical forest restoration worldwide, aiming to identify knowledge gaps and where research is concentrated. We compiled scientific articles on tropical forest restoration in English, available in Scopus, and analyzed them through time via citation counts, topic, biome, country, and authorship networks. We found 1476 articles with 38,038 citations, indicating that we have accumulated a great amount of scientific knowledge on tropical forest restoration so far, especially in the last 15 years (89% of all articles). However, publications are unequally distributed. Whereas articles were published in 71 of 120 tropical countries/territories, Brazil (376 articles), Mexico (163 articles), and Costa Rica (116 articles) accounted for 44% of publications. There was also a disparity in authorship; some countries have mostly lead authors belonging to national institutions while others have mostly foreign lead authors. Montane and dry forests were notably less studied than lowland and wet forests. The most studied topics were the technical, ecological, and biophysical aspects of restoration (83% of articles). Publication counts incompletely represent accumulated knowledge, but our results provide an indication of relative scholarship across biomes, topics, political units, and scientific leadership roles. From these, future research will be justified in moving forward in the areas of climate change, sociology, culture, and economics, and with local scientific leadership, particularly in Africa.